Description and features of risky alcohol drinking behaviour - Vardar, Erdal (Journal of Dependence, 2016)
Today, alcohol is one of the most popular substances in the world. There are various characteristics of alcohol consumption behaviour person to person. Also, there are social differences in consumption behaviours between the countries. The consumption of four to five drinks in a single occasion is a Risky single-occasion drinking (RSOD) behaviour sample. RSOD is more common in late adolescence and early adulthood. Recently, it was depicted that RSOD has remarkable possible and negative health effects. Especially adolescent and young people consume alcohol as a risky drinking behaviour for joyful activities. This is also the age when young people in most countries are legally allowed to buy and drink alcohol, but they usually do not yet have adult responsibilities. For these reason, adolescents are the most risky group for the RSOD behaviour. Finally, this subject draw more interest because of the adolescent have a lot of hospital admission due to alcohol intoxication, negative health effects and legal issues. In this paper, the literature was reviewed about RSOD and Suggestion was provided for prevention of the RSOD.
Keywords: Alcohol; addiction; relative risk; alcohol drinking; drinking behaviour; binge drinking